2019
DOI: 10.1177/1440783319836281
|View full text |Cite
|
Sign up to set email alerts
|

Chinese business migrants in Australia: Middle-class transnationalism and ‘dual embeddedness’

Abstract: Over the past two decades, four-fifths of the business immigration to Australia originated from China. Australian business migrants are required to undertake a two-step migration pathway: first they demonstrate a certain level of assets and business success to qualify for temporary entry and then, through successful business activity, they qualify for permanent residency (PR). Using in-depth interview narratives and survey data, this article explores migration motives and experiences of Chinese business migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although the “entrepreneur” label is linked to investment and wealth accumulation goals, the structural conditions of both home and host countries show that the reasons for migration are beyond economic motives and aspirations. Some of the other motives are educational opportunities, safety, and transparency, validating professional careers and securing permanent residency rights (Colic‐Peisker & Denk, 2019). These motivations influence the immigrant's level of adjustment, integration and career success in the host country (Cerdin, Diné, & Brewster, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the “entrepreneur” label is linked to investment and wealth accumulation goals, the structural conditions of both home and host countries show that the reasons for migration are beyond economic motives and aspirations. Some of the other motives are educational opportunities, safety, and transparency, validating professional careers and securing permanent residency rights (Colic‐Peisker & Denk, 2019). These motivations influence the immigrant's level of adjustment, integration and career success in the host country (Cerdin, Diné, & Brewster, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, some immigrant entrepreneurs move to another country for a better life for themselves and their children. Therefore, they keep their dependence on their already profitable home country businesses, resulting in stronger dual embeddedness (Colic-Peisker and Deng, 2019).…”
Section: Beyond Embedded or Not Embeddedmentioning
confidence: 99%
“…Some even claim that dual embeddedness may speed up the integration process (Ren and Liu, 2015). For example, Chinese immigrants in Singapore (Ren and Liu, 2015), Germany (Leung, 2003), the UK (Quan et al , 2019) and Australia (Colic-Peisker and Deng, 2019; Liang, 2019) have experienced dual embeddedness in their social and institutional contexts. In addition, some immigrant entrepreneurs move to another country for a better life for themselves and their children.…”
Section: Embeddedness Levels Of Immigrant Entrepreneursmentioning
confidence: 99%
“…Rather, scholars have found that middling migrants move for a combination of reasons involving economics, lifestyle and even for self-development. As such, the literature on middling migrants has looked at skilled professionals (Beaverstock, 2011; Colic-Peisker & Deng, 2019; Ho, 2011; Wee & Yeoh, 2021) and middle-class youths seeking overseas adventures on ‘working holidays’ (Clarke, 2005, Robertson, 2013). This work is significant in contributing to understanding of migrants who are ‘wedged’ between the ‘highly skilled’ and ‘low-skilled’ migrant workers.…”
Section: Introduction: Theorising the ‘Middle’mentioning
confidence: 99%
“…The middling literature, however, has a large concentration on ‘white’ migrants (Beaverstock, 2011; Collins, 2014; Conradson & Latham, 2005; Scott, 2006; Wiles, 2008;) and gendered analyses are overtly focused on women (Kofman, 2012; Main, 2016; Tu & Xie, 2020). Literature on Asian middling migrants is relatively sparse, though this has been growing in recent years (Baas, 2017; Colic-Peisker & Deng, 2019 Jaskułowski, 2017; Robertson, 2019; Wee & Yeoh, 2021).…”
Section: Introduction: Theorising the ‘Middle’mentioning
confidence: 99%